Capacity, OUtpL!t, and Sequential Entry: Comment - Reynolds, Stanley S. (American Economic Review, 1985)
Two behavioral assumptions that are often made in the industrial organization literature are that an established firm (or group) may deter entry either through limit pricing (the Sylos Postulate) or by holding excess capacity (the Excess Capacity Hypothesis). In an interesting recent article in this Review (1981), Daniel Spulber examines these behavioral assumptions to see whether they are consistent with rational behavior by an established firm. Spulber's analysis is based on a two-firm, two-period game model in which the established firm is given a first-in advantage. By introducing this dynamic element into the model, Spulber is able to explicitly address the issue of the optimality of entry-deterring behavior. Spulber finds that the use of limit pricing and/or excess capacity to deter entry is rational only under a very limited set of circumstances.' In particular, when the second-period outcome is determined by a Cournot-Nash equilibrium, he derives the following results. 1) The first-period output of the established firm is always less than or equal to the first-period output produced by a firm not anticipating entry. The established firm essentially accommodates entry and limit pricing does not occur. 2) The established firm never holds more capital than the amount that would minimize its production costs, given its output choices in periods one and two. This comment takes issue with Spulber's conclusions about the Cournot-Nash case. It will be shown that the two results cited above may be reversed when the production technology is characterized by variable proportions. This reversal hinges on the particular type of Nash equilibrium employed in the analysis of the two-period model. Spulber implicitly uses a Nash equilibrium that is not subgame perfect.2 It is shown below that, when one requires the Nash equilibrium to be subgame perfect, both limit pricing and excess capital investment outcomes are possible for the variable proportions technology case. The subgame perfection property thus seems to capture an important strategic element in decision making for the established firm. In some cases, this type of strategic behavior leads to entry barriers that would not exist under innocent profit maximization by the established firm. Strategic entry barriers are discussed by Steven Salop (1979). Spulber's notation and assumptions about demand and costs are adopted below.